Heart rate variability and serum level of insulin-like growth factor-1 are correlated with symptoms of emotional disorders in patients suffering a mild traumatic brain injury. Issue 2 (February 2016) - Sung, Chih-Wei; Chen, Kai-Yun; Chiang, Yung-Hsiao; Chiu, Wen-Ta; Ou, Ju-Chi; Lee, Hsin-Chien; Tsai, Shin-Han; Lin, Jia-Wei; Yang, Che-Ming; Tsai, Yan-Rou; Liao, Kuo-Hsing; Chen, Gunng-Shinng; et al.
Highlights: Reduced heart rate variability (HRV) was noted in patients with mild traumatic brain injury (mTBI). The power spectrum of HRV was positively correlated with serum levels of IGF-1 in mTBI patients. Early HRV can be noninvasively measured to assess anxiety and depression symptoms in mTBI patients. Abstract: Objective: Patients who have experienced a mild traumatic brain injury (mTBI) are susceptible to symptoms of anxiety or depression. To explore the potential biomarkers for emotional disorders in mTBI patients, we analyzed the frequency domain of heart rate variability (HRV) and serum concentrations of four neurohormones. Methods: We assessed mTBI patients on their first visit and follow-up. Symptoms were evaluated by the Beck Anxiety Inventory and the Beck Depression Inventory, respectively. Serum levels of adrenocorticotropic hormone (ACTH), melatonin, cortisol, and insulin-like growth factor (IGF)-1 and HRV follow-ups were measured and compared. Results: mTBI patients were more vulnerable to symptoms of anxiety or depression than healthy controls. Reduced HRV was noted in mTBI patients compared to healthy controls. The mTBI patients demonstrated higher serum levels of ACTH, lower IGF-1 compared to healthy controls. In correlation analysis, only IGF-1 was positively correlated with HRV in mTBI patients. Both HRV and IGF-1 were correlated with symptom of depression while only HRV was correlated with symptom of anxiety in mTBI patients. Conclusions: We infer that HRV may be more significantly correlated with emotional disorders than is IGF-1 in mTBI patients. Significance: The study is relevant for specific diagnostic markers in mTBI patients.